Production of high-fructose syrup from cassava starch - Brillantes, Ma. Rowena H.; Ladia, Jon Ferbennman J.; Vasquez, Jimmy P. (Diliman, Quezon City College of Engineering, 1993)
Plant capacity: 27,565 kg HFCaS/day -- Plant location: Sta. Rosa, Laguna -- Plant area: 2521.5 sq.m. -- Total capital investment: P 25,000,000.00 -- Annual cost of production: P 210,879,000.00 -- Annual sales: P 231,547,428.00 -- Annual income (after tax): P 13,434,478.00 -- Rate of return on investment (after tax): 53.74% -- Payback period: 1.86 years
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Agricultural processing plants; Cassava; Fructose